Management Of Strengthening Student Character Education To Realize The Students Graduates Quality In Spk-Sma Saint John’s Catholic School And Insan Cendekia Madani Sma - Susanto, FX.; Wasliman, Iim; Sudrajat, Adjat; Mulyanto, Agus (International Journal of Science, Technology & Management, 2022)
The This research is driven by the problems in implementing character education at school which have not yet met the expectations. It is closely related to the management of strengthening character education which plays an important role but has not been implemented effectively. The research was conducted with a qualitative approach-case study method. Data collection techniques were carried out through: (1) in-depth interviews, (2) direct observations, and (3) documentation studies. In general, this study aims to identify and analyze the management of strengthening character education to produce the quality graduates. Specifically, it is also to find out and analyze: (1) the planning process, (2) implementation, (3) evaluation, (4) follow-ups, (5) problems, (6) solutions, and (7) results of strengthening character education related to the quality of graduates at Saint John's Catholic School and Insan Cendekia Madani High School, South Tangerang City, Banten.The theoretical foundation used is Total Quality Management (TQM). As an approach, TQM is expected to to raise the quality of graduates with strong characters and thus, increase the customer satisfaction, improved quality, and commitment. To improve the quality, the Deming Cycle or PDCA (Plan, Do, Check, and Act) method is used to ensure any deviation or failure to be detected and corrected quickly. Hence, the efforts to strengthen character education have an impact to the students, not only the cognitive aspect (moral knowing), but also the affective (moral feeling), and psychomotor (moral behavior). The results of this study indicate that: (1) The management planning for strengthening character education has referred to the vision, mission, goals, and values of the school. It is necessary to clarify the order of priority to solve the occuring problems. (2) The implementation of strengthening character education has been going well. However, school principals need to improve coordination with parents and the community, develop teacher professionalism and supervise consistently and continuously. (3) The evaluation has been carried out in accordance with the assessment steps. Aspects of strengthening character have been carried out well, i.e religious teachings and beliefs, which emphasizes on respecting diversity, and increasing student learning abilities. It is necessary to improve the aspects of moral values in compliance with social rules. (4) Follow-ups have been carried out based on the evaluation results to take corrective actions for standardisation purpose.